The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1128/jb.140.1.161-166.1979
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity to Hg2+ and hyperbinding activity associated with cloned fragments of the mercurial resistance operon of plasmid NR1

Abstract: The region of plasmid NR1 concerned with resistance to Hg2' and organomercurials consists of sequences found on restriction endonuclease fragments EcoRI-H and EcoRI-I. When both fragments were cloned together into a derivative of plasmid ColEl, the hybrid plasmid conferred properties indistinguishable from those of the parental plasmid, NR1: resistance to Hg2' and to the organomercurials merbromin and fluoresceinmercuric acetate and the inducible synthesis of the enzyme mercuric reductase. When fragment EcoRI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…This effect was not observed with either copC or copD expressed alone. Similar observations led to the discovery of a mercury transport system encoded by merT and merP associated with mercury resistance [30,31]. Preliminary uptake studies indicated that cells containing copCD accumulated more copper than cells without these genes or with either copC or copD alone [23].…”
Section: Cellular Copper Uptakementioning
confidence: 73%
“…This effect was not observed with either copC or copD expressed alone. Similar observations led to the discovery of a mercury transport system encoded by merT and merP associated with mercury resistance [30,31]. Preliminary uptake studies indicated that cells containing copCD accumulated more copper than cells without these genes or with either copC or copD alone [23].…”
Section: Cellular Copper Uptakementioning
confidence: 73%
“…Work on the mechanism of HgR led to identi¢cation of the key detoxi¢cation enzyme, MerA, the mercuric ion reductase [12], and also of a second enzyme, MerB, which split the carbon^Hg bond in such compounds as the disinfectant phenylmercuric acetate (PMA) and the fungicide methylmercury chloride, a potent neurotoxic agent [13]. Membrane and periplasmic proteins involved in the seemingly paradoxical inward transport of ionic mercury [14,15] were also identi¢ed [16,17]. The ¢rst sequences of HgR loci revealed proteins corresponding to these biochemical and physiological functions as well as a candidate regulatory gene (merR).…”
Section: A Brief History Of the Study Of Mercury Resistancementioning
confidence: 99%
“…The existence of an operon-speci¢c Hg(II) uptake system was ¢rst suggested on the basis of the Hg(II)-hypersensitive phenotype of merA mutants [14,15]; such variants were more sensitive to Hg(II) than cells lacking the operon altogether, consistent with there being some mechanism for bringing Hg(II) into the cell. In the absence of the mercuric reductase, the internalized Hg(II) is not de-toxi¢ed by reduction to Hg(q).…”
Section: Transportmentioning
confidence: 99%
See 2 more Smart Citations